Optimizing Continuous Glucose Monitoring Adoption in India: From Current Challenges to Future Solutions. - Kesavadev, Jothydev; Mohan, V.; Joshi, Shashank; Saboo, Banshi; Chawla, Manoj; Unnikrishnan, A. G.; Lakhani, Om; Gupta, Amit; Parikh, Rakesh; Bhograj, Abhijith; Maheshwari, Anuj; Joshi, Ameya; et al. (Diabetes Therapy, 2026)
Despite revolutionizing diabetes care globally, continuous glucose monitoring (CGM) adoption in India remains limited, as a result of several economic, infrastructural, clinical, and sociocultural concerns. This narrative review aims to map unmet needs and propose practical, context-specific solutions. Continuous use of CGM remains the preferred approach for optimal glucose management and achieving long-term metabolic advantages, providing insights for proactive, data-driven, and preventive diabetes care. However, main barriers to CGM uptake include limited awareness among people with diabetes and healthcare providers, high costs, lack of reimbursement, limited device availability beyond major cities, and economic, infrastructural, and sociocultural access inequities across urban and rural populations. The psychological burden from frequent alarms, data fatigue, and stigma with noticeable or intrusive devices add to these challenges. Addressing these barriers necessitates a multifaceted strategy involving affordable, climate-adapted devices, interoperable digital ecosystems, India-specific reimbursement models, and robust educational infrastructure. The emergence of cost-effective CGM devices with a range of advanced features, such as predictive glucose algorithms and personalized pattern identification, is pivotal to this effort. These innovations improve clinical outcomes and quality of life by simplifying the user experience, addressing challenges, such as alarm fatigue while translating complex data into actionable insights, facilitating widespread CGM adoption in India. Plain Language Summary: This review examines why the uptake of continuous glucose monitoring (CGM) is poor in India, despite its advantages observed in people with diabetes. It discusses typical challenges, including high costs, inadequate infrastructure beyond major cities, and limited awareness among patients and healthcare providers. This review also emphasizes the importance of optimizing the current CGM solutions for people with diabetes to monitor their glucose levels, reduce stress, and help with better diabetes management. It further highlights the need for improved training for healthcare providers and care teams and patient-centred education. By combining enhanced technology, supportive health systems, and practical policies, this review outlines strategies to make CGM more accessible and useful for people with diabetes across India.